Magneto- and opto-stimuli responsive nanofibers as a controlled drug delivery system. (6th October 2021) - Banerjee, Aihik; Jariwala, Tanvi; Baek, Youn-Kyung; To, Dung Thi Hanh; Tai, Youyi; Liu, Junze; Park, Hyle; Myung, Nosang V; Nam, Jin
Abstract: The drawbacks of conventional drug administration include repeated administration, non-specific biodistribution in the body's systems, the long-term unsustainability of drug molecules, and high global cytotoxicity, posing a challenge for the efficient treatment of chronic diseases that require varying drug dosages over time for optimal therapeutic efficacy. Most controlled-release methods encapsulate drug molecules in biodegradable materials that dissolve over time to release the drug, making it difficult to deliver drugs on a schedule. To address these limitations, we developed a magneto-, opto-stimuli responsive drug delivery system based on functionalized electrospun nanofibers loaded with superparamagnetic iron oxide nanoparticles (SPIONs). We exploited the Néel relaxation effect of SPIONs, where heat generated from vibrating SPIONs under exogenously applied magnetic fields or laser illumination induced structural changes of the thermo-sensitive nanofibers that encapsulate the particles. We showed that this structural change of nanofibers is the governing factor in controlling the release of dye molecules, used as a model drug and co-encapsulated within the nanofibers. We also showed that the degree of nanofiber structural change depends on SPION loading and duration of stimulation, demonstrating the tunability of the drug release profile. Overall, we demonstrated the potential of SPION-embedded thermoplastic nanofibers as an attractive platform for on-demand drug delivery.